2023
DOI: 10.1098/rstb.2022.0149
|View full text |Cite
|
Sign up to set email alerts
|

Evolution at the arid extreme: the influence of climate on sand termite colonies and fairy circles of the Namib Desert

Abstract: In the hyperarid Namib Desert, the sand termite Psammotermes allocerus Silvestri, 1908 (Isoptera: Rhinotermitidae) establishes colonies that create conspicuous, barren patches known as ‘fairy circles' on permeable, sandy soils. The central bare areas of fairy circles serve the key function of storing moisture received from sparse rainfall. The sandy soil texture allows rapid infiltration and percolation of precipitation, while localized herbivory by the termites creates the bare patch, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
(118 reference statements)
2
4
0
Order By: Relevance
“…The soil water diffusion coefficient, W D , is also larger for the coarser grains. A numerical simulation of a model for the Namibian FC showed that the FC size increases with W D [13], in agreement with our new finding.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The soil water diffusion coefficient, W D , is also larger for the coarser grains. A numerical simulation of a model for the Namibian FC showed that the FC size increases with W D [13], in agreement with our new finding.…”
Section: Resultssupporting
confidence: 90%
“…These vegetation patterns can survive drier conditions than the uniform vegetation and they are very important for the ecological system in these harsh environments [4]. A recent work, based on remote sensing analysis [7], claimed that FC-like patterns are globally distributed, and discovered 263 new sites of vegetation gaps, but more detailed field work is needed to understand the formative mechanisms (physical Land 2024, 13,197 2 of 14 and ecological) at these new sites and to distinguish between FC-like patterns (vegetation gaps) to proper FCs [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Juergens et al . [ 63 ] now further show that the largest termite nests are located underneath the bare patches within the fairy circles, whilst smaller nests are located outside of fairy circles and thus have direct access to grass tussocks as food [ 63 ].…”
Section: Large Communal Nests In Harsh Environmentsmentioning
confidence: 99%